2012
DOI: 10.1111/j.1749-7345.2012.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Use of Fatty Acids in Fish Farming Research during the Last Decade, with Particular Emphasis on Fish Quality

Abstract: The present literature overview was carried out in order to assess the use of fatty acids (FA) analysis in fish farming research during the last decade. As aquaculture products are mainly intended for human consumption, the overview is focused on fish fillet, carcass or whole body FA, as a major aspect of fish nutritional value. This survey used 394 papers and demonstrated that a) 71% of papers report FA as relative percentage of total FA (% totFA), b) 23% of papers report actual FA amounts, c) in 63% of paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 401 publications
1
12
0
Order By: Relevance
“…To do so, relatively minor and easily implemented modifications to commonly used laboratory protocols have to be considered, and briefly including: accurate weight of samples, complete lipid extraction, use of known amounts of proper selected internal standard, complete chromatography resolution and reporting, appropriate transformations and/or calibration with external standards. These are technical, but important, aspects that have been widely discussed and detailed information are readily available [53][54][55]59]. Therefore, a proper quantitative fatty acid analysis is absolutely necessary, even before attempting a study on this topic, and also detailed information about methodologies used should always be reported, so that reviewers, and then readers, would be able to fully understand and ponder the results proposed in the study itself.…”
Section: Analytical Chemistry Methodologiesmentioning
confidence: 98%
See 2 more Smart Citations
“…To do so, relatively minor and easily implemented modifications to commonly used laboratory protocols have to be considered, and briefly including: accurate weight of samples, complete lipid extraction, use of known amounts of proper selected internal standard, complete chromatography resolution and reporting, appropriate transformations and/or calibration with external standards. These are technical, but important, aspects that have been widely discussed and detailed information are readily available [53][54][55]59]. Therefore, a proper quantitative fatty acid analysis is absolutely necessary, even before attempting a study on this topic, and also detailed information about methodologies used should always be reported, so that reviewers, and then readers, would be able to fully understand and ponder the results proposed in the study itself.…”
Section: Analytical Chemistry Methodologiesmentioning
confidence: 98%
“…These analytical considerations and concerns have been, for example, recently raised specifically for fish and seafood products, where typically n-3 LC-PUFA are the key objects of the analysis of the studies [55].…”
Section: Analytical Chemistry Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with the scatter plot analysis of residuals where a continuous (homogenous) distribution of plotted values along the X ‐axis was found regardless of the species subgroup. However, scaling up the predictive model to other fish species and/or experimental conditions is difficult, because precise information on fillet lipid content and FA composition is not always available, as highlighted by the recent literature overview of more than 390 scientific publications (Karakatsouli ). This is not the case for the data used in the present study, and it can be predicted that the fillet content in n‐3 LC‐PUFA is of the same order of magnitude at a marketable size of 2.5 kg for turbot and 500 g for sole and gilthead sea bream.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that S. platensis strain LEB-18 very well applied in feed to overcome nutritional deficiencies because they contain a variety of minerals and other nutritional components (carbohydrates, fat and fiber, protein and ash). Changes fat and protein content in body fish associated with altered synthesis and deposition levels in the muscle (Abdel-Tawab & Ahmed, 2009;Karakatsouli, 2012).…”
Section: Body Composition Of Gurami Feed With Experimental Dietsmentioning
confidence: 99%